Medical applications of artificial intelligence - Agah, Arvin (CRC Press, 2014)
"Artificial Intelligence techniques have been successfully applied to the medical domain, and AI systems are being integrated into healthcare. AI systems can make providing healthcare more accurate, less expensive, more available, and more efficient. They are consistent and can be mass produced. This book includes a number of contributed chapters that detail the most recent advances and research efforts by world-wide experts in the field. The chapters follow the organization of the taxonomy; and offer a clear connection between chapters"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Artificial Intelligence; Medical Informatics